The Practice of Hajj Substitution in Indonesia: The Search for Legal Certainty through Usul al-Fiqh Approach - Nurdin, Roswati; Rajab, H. (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2020)
This article discusses the issue of legal certainty of the practice of hajj substitution (badal haji) in Indonesia for the prospective pilgrims who have died before the pilgrim season or have suffered from chronic diseases hindering them from performing the planned hajj from the perspective of uá¹£Å«l al-fiqh approach. Despite the fact that Hajj substitution has been widely practiced, there are problems with regards to both legal basis and actual practices. From the fiqh point of view, the issue is subject to dissent between the scholars and jurists. As for its actual practice, there is a wide opportunity for abuse from irresponsible parties. Along with this background, in seeking for legal certainty, this article employs bayÄnÄ« (textual), taÊ»lÄ«lÄ« (causation), and istiá¹£lÄá¸¥Ä« (public interest) reasoning of uá¹£Å«l al-fiqh upon the relevant literature. Through bayÄnÄ« reasoning, this article concludes that hajj substitution is obliged by some texts of hadith. TaÊ¿lÄ«lÄ« reasoning reveals that the obligation applies only to the people who are at some point had reached the level of istiá¹ÄÊ¿a in their life. Finally, istiá¹£lÄá¸¥Ä« reasoning unveils a number of adverse situations that one should take into consideration when planning for a hajj substitution on behalf of another, such as the issue of trust with the substitute of the hajj. Accordingly, this article argues that hajj substitution is allowed to be performed under the specific provision and trustworthiness.